Analysis of the Effect of Work From Home and the Use of Information Technology on Employee Performance Through Job Satisfaction as Intervening Variable (Study at the Lumajang Regional Forestry Service Branch and Jember Regional Forestry Service Branch) - Sriyaningsih Sriyaningsih; Ni Nyoman Putu Martini; Nursaid Nursaid (International Journal of Management Science and Information Technology, 2022)
The purpose of this study was to determine directly or indirectly the effect of work from home and the use of information technology on employee performance through job satisfaction as an intervening variable (study at the Lumajang District Forestry Service Branch and Jember District Forestry Service Branch). The number of samples is 78 people. The analytical technique used is WarpPLS 5.0. The results of data analysis show that: 1). The work from home variable has a positive and insignificant effect on both job satisfaction and employee performance of 0.210; 2). The variable of the use of information technology has a positive and significant effect on both job satisfaction and employee performance of 0.074; 3). The satisfaction variable has a positive and significant effect on employee performance of 0.001; 4). Information technology has a positive and significant effect on employee performance of 0.001; 5). job satisfaction has a positive and significant effect on employee performance of 0.001; 6) There is an indirect effect of work from home on employee performance variables through employee job satisfaction whose value is smaller than the direct effect, also not significant at 0.188 with details of the direct effect of 0.158 and the indirect effect of 0.074; 7). There is an indirect effect of the variable use of information technology on employee performance through job satisfaction whose value is smaller than the direct effect of 0.54 with details of the direct effect of 0.386 and the indirect effect of 0.177.